Biomass and lipid production by the native green microalgae Chlorella sorokiniana in response to nutrients, light intensity, and carbon dioxide: experimental and modeling approach - Montoya-Vallejo, Carolina; Guzmán Duque, Fernando León; Quintero Díaz, Juan Carlos (Frontiers in Bioengineering and Biotechnology, 2023)
Microalgae are photosynthetic cells that can produce third generation biofuels and other commercial compounds. Microalgal growth is influenced by two main parameters: light intensity and carbon dioxide concentration, which represent the energy and carbon source, respectively. For photosynthesis, the optimum values of abiotic factors vary among species. In this study, the microalgae Chlorella sorokiniana was isolated from a freshwater lake. It was identified using molecular analysis of the Ribosomal Internal Transcribed Spacer. A single-factor design of experiments in 250-mL Erlenmeyer flasks was used to evaluate which concentrations of nitrogen and phosphorus increase the production of biomass and lipids. The Response Surface Methodology was used with a 32-factorial design (light intensity and CO2 was used to evaluate its effect on biomass, lipid production, and specific growth rates, in 200mL tubular photobioreactors (PBR)). Low levels of light lead to lipid accumulation, while higher levels of light lead to the synthesis of cell biomass. The highest biomass and lipid production were 0.705±0.04g/L and 55.1±4.1% respectively. A mathematical model was proposed in order to describe the main phenomena occurring in the culture, such as oxygen and CO2 mass transfer and the effect of light and nutrients on the growth of the microalgae. The main novelties of this work were the molecular identification of the strain, the optimization of culture conditions for the indigenous microalgae specie that was isolated, and the formulation of a model that describes the culture`s behavior.